Pollination by bats enhances both quality and yield of a major cash crop in Mexico. Issue 3 (26th December 2019) - Tremlett, Constance J.; Moore, Mandy; Chapman, Mark A.; Zamora‐Gutierrez, Veronica; Peh, Kelvin S.‐H.
Abstract: Bats pollinate many plants of high socio‐economic value, including the majority of columnar cacti (Cactaceae) in Mexico, which have been used by humans for food and materials for thousands of years. However, the importance of bats as pollinators has been overlooked, with a consequent lack of knowledge of the reliance of crops on bats for harvest yield and quality. We used exclusion experiments to determine the effect of different pollinator taxa on the yield and quality of pitayas (fruit of Stenocereus queretaroensis (F.A.C. Weber) Buxbaum), a major crop in central Mexico. We studied the three most economically important cultivars and wild individuals in the principal region for pitaya production. For each pollinator taxon we recorded fruit set and measured three key parameters of fruit quality: weight, sucrose concentration and seed set. We placed camera traps to determine pollinator identity and the effect of visitation rate on fruit quality. We found the primary pollinators of pitayas to be nectarivorous bats in the genus Leptonycteris . When bats were excluded from flowers and flowers were pollinated by other taxa (i.e. diurnal birds and insects), pitaya yield decreased by 35%, though pollination dependence varied between cultivars. Fruit quality decreased significantly in the absence of bat pollination across all cultivars, with fruits 46% lighter and 13% less sweet when pollinated by other taxa; reducing economic value, as size determines market price. Additionally, seed set (an indicator of effective pollination) was significantly lower in the absence of bat pollinators. Visitation rate had no effect on fruit quality. Synthesis and applications. Our study shows that bats provide a vital ecosystem service by pollinating a crop of major socio‐economic importance, and that consideration of both crop quality and yield are essential to fully understanding the benefits of bat pollination. A reduction of this service would result in a decrease in both the size and quality of the harvest, causing substantial loss of income for rural communities. Bats world‐wide face many threats, and management efforts targeted to the enhancement of wild bat pollinator populations would preserve the sustainability of both bat‐pollinated crops and wild plants. Abstract : Our study shows that bats provide a vital ecosystem service by pollinating a crop of major socio‐economic importance, and that consideration of both crop quality and yield are essential to fully understanding the benefits of bat pollination. A reduction of this service would result in a decrease in both the size and quality of the harvest, causing substantial loss of income for rural communities. Bats world‐wide face many threats, and management efforts targeted to the enhancement of wild bat pollinator populations would preserve the sustainability of both bat‐pollinated crops and wild plants. Editor's Choice Resumen: Los murciélagos polinizan un gran número de plantas de gran valor socioeconómico, incluyendo la mayoría de los cactus columnares (Cactaceae) en México, los cuales han sido utilizados por los humanos durante miles de años para obtener alimento y materiales. Sin embargo, se ha pasado por alto la importancia de los murciélagos como polinizadores, con la consiguiente falta de conocimiento de la dependencia de los cultivos a la polinización por los murciélagos para el rendimiento y calidad de la cosecha. Utilizamos experimentos de exclusión para determinar el efecto de diferentes taxones polinizadores en el rendimiento y la calidad de las pitayas (fruto de Stenocereus queretaroensis (F.A.C. Weber) Buxbaum), un cultivo importante en el centro de México. Estudiamos los tres cultivares más importantes económicamente e individuos silvestres, en una de las regiones más importantes para la producción de pitaya. Para cada taxón polinizador registramos la producción de frutas y medimos tres parámetros clave de la calidad del fruto: peso, concentración de sacarosa y cantidad de semillas. Colocamos cámaras trampa para determinar la identidad de los polinizadores y el efecto de la tasa de visitas en la calidad de la fruta. Encontramos que los principales polinizadores de las pitayas son los murciélagos nectarívoros del género Leptonycteris . Cuando los murciélagos fueron excluidos de las flores y éstas fueron polinizadas por otros taxones (es decir, aves e insectos diurnos), el rendimiento de las pitayas disminuyó en un 35%, aunque esta dependencia de polinización varió entre los cultivares. La calidad de la fruta disminuyó significativamente en ausencia de la polinización de murciélagos en todos los cultivares, con frutas 46% más livianas y 13% menos dulces cuando se polinizaron por otros taxones, reduciendo así el valor económico ya que su tamaño determina su precio en el mercado. Adicionalmente, el número de semillas (un indicador de polinización efectiva) fue significativamente menor en ausencia de los murciélagos polinizadores. La tasa de visitas no tuvo efecto sobre la calidad del fruto. Síntesis y aplicaciones. Este estudio muestra que los murciélagos proporcionan un servicio ecosistémico vital al polinizar un cultivo de gran importancia socioeconómica, y que la consideración de la calidad y el rendimiento del cultivo son esenciales para comprender completamente los beneficios de la polinización de los murciélagos. Una reducción de este servicio resultaría en una disminución tanto en el tamaño como en la calidad de la cosecha, causando una pérdida sustancial de ingresos para las comunidades rurales. Los murciélagos en todo el mundo enfrentan muchas amenazas y los esfuerzos de manejo dirigidos a la mejora de las poblaciones de murciélagos polinizadores apoyarían a la conservación tanto de los cultivos polinizados por murciélagos como de las plantas silvestres.